GAMBARAN PERILAKU MEROKOK ORANG TUA YANG MEMILIKI ANAK: BAYI DAN BALITA - Sri Maharani; Riri Novayelinda; Wasisto Utomo (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2022)
The smoking behavior of parents in the house can cause various diseases for active and passive smokers (people around smokers), especially infants and toddlers. The purpose of this study was to describe the smoking behavior of tau people who have children: babies and toddlers. The method used is descriptive using a retrospective approach with the number of respondents, namely 230 parents who have aged 0-5 years. The sample was obtained using accidental sampling method. Methods of data collection by filling out a questionnaire. The results showed that parents who have babies (35.6%), toddlers (45.7%), pre-school (18.7%), parents who have education (father), did not complete elementary school (1, 3%), elementary school (10.4%), junior high school / equivalent (30.1%), high school / equivalent (43.9%), tertiary education (14.3%), knowledge of parents about children's health: infants and toddlers are good (6.5%), sufficient (28.7%), lacking (64.8%), knowledge about smoking is good (77.8%), sufficient (21.3%), less (0.9%) ), type of cigarette smoked, kretek (%), filter (%), others (%), location of family members when smoking, regardless of location when smoking (66.1%), paying attention to location when smoking (33.9%) , the number of family members who smoke in the house regardless of location when smoking, is only 1 person (76.3%), 2 people (20.4%), 3 people (3.3%), light smokers (11.2%) ), moderate smokers (41.4%), heavy smokers (47.4%). Many parents have the habit of smoking near babies and toddlers even though the level of parents' knowledge about the dangers of smoking is good. Keywords: Babies, toddlers, knowledge, smoking behavior